2014
DOI: 10.1152/ajpcell.00130.2013
|View full text |Cite
|
Sign up to set email alerts
|

Activin A induction of erythroid differentiation sensitizes K562 chronic myeloid leukemia cells to a subtoxic concentration of imatinib

Abstract: Chronic myeloid leukemia (CML) is a hematopoietic stem/progenitor cell disorder in which Bcr-Abl oncoprotein inhibits cell differentiation. Differentiation induction is considered an alternative strategy for treating CML. Activin A, a member of the transforming growth factor-β superfamily, induces erythroid differentiation of CML cells through the p38 MAPK pathway. In this study, treatment of the K562 CML stem/progenitor cell line with activin A followed by a subtoxic concentration of the Bcr-Abl inhibitor ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…It is well-documented that p38 MAPK was involved in the erythroid differentiation of K562 cells;2,17,18 here consistently we observed that ee-As 4 S 4 increased the expression of p-p38 MAPK in K562 cells after 72 hr incubation (Figure 2E). When a p-38 inhibitor SB202190 was supplemented in the culture medium, the expression level of CD235a went down (Figure 2F), demonstrating that ee-As 4 S 4 induced erythroid differentiation through the phosphorylation of p38 MAPK.…”
Section: Resultssupporting
confidence: 76%
“…It is well-documented that p38 MAPK was involved in the erythroid differentiation of K562 cells;2,17,18 here consistently we observed that ee-As 4 S 4 increased the expression of p-p38 MAPK in K562 cells after 72 hr incubation (Figure 2E). When a p-38 inhibitor SB202190 was supplemented in the culture medium, the expression level of CD235a went down (Figure 2F), demonstrating that ee-As 4 S 4 induced erythroid differentiation through the phosphorylation of p38 MAPK.…”
Section: Resultssupporting
confidence: 76%
“…No effect of activin A treatment on the response to seven anticancer drugs (cisplatin, carboplatin, doxorubicin, taxol, SN38, terarubicin and etoposide) was found, in contrast, in an ovarian adenocarcinoma cell line, but a cisplatin-resistant derivative showed decreased activin A sensitivity by loss of activin receptor type 2 expression [81]. In diffuse large B-cell lymphoma, ectopic expression of activin A resulted in reduced cell growth and enhanced chemosensitivity [45], and in the Bcr-Abl-positive chronic myeloid leukemia cell line K562, activin A-induced differentiation sensitized the cells to imatinib treatment [82]. Apart from the K562 cell model, however, the impact of activin A on the response to kinase inhibitors or other targeted cancer therapeutics has remained largely unexplored so far.…”
Section: Activin a In Stemness And Drug Resistancementioning
confidence: 99%
“…We used an established method to measure soluble (depolymerized) and assembled (polymerized) tubulin [14]. After treatment, K562 and K562R cells were lysed with 200 ll of a lysis buffer (20 mM Tris-HCl at pH 6.8, 1 mM MgCl 2 , 2 mM EGTA, 1 mM PMSF, 1 mM orthovanadate, 0.5 % NP-40, and 20 lg/ml each of the proteinase inhibitors aprotinin, leupeptin, and pepstatin) and centrifuged at 12,000 9 g for 10 min at 4°C.…”
Section: Measurement Of In Vivo Microtubule Assemblymentioning
confidence: 99%
“…Western blotting was performed after total cell lysates were extracted, as described previously [14]. To detect specific proteins, the following antibodies were used according to the manufacturer's guidelines: a-tubulin and horseradish peroxidase-conjugated secondary antibodies (Sigma); procaspase-9, procaspase-3, cleaved caspase-3, PARP, cyclin B1, phospho-Cdc2, phospho-c-Abl, c-Abl, phospho-AKT, AKT, phospho-MAPK, MAPK, and Bcl-2 (Cell Signaling, Danvers, MA.…”
Section: Western Blottingmentioning
confidence: 99%